Komunikasi Sosial Generasi Milenial di Era Industri 4.0 - Nurdin, Ali; Labib, Mufti (Communicatus: Jurnal Ilmu komunikasi, 2021)
The purpose of this study is to describe the social communication process of the millennial generation in the midst of the folds of virtual space based on industry 4.0. This study uses a descriptive-qualitative type to describe the social communication behavior tendencies of the millennial generation. Data collection was carried out by distributing semi-open questions randomly through the Google Form application to the millennial generation in Surabaya. The results of the study explain that the millennial generation's social communication process is carried out in three stages; first, building social communication on the basis of social media and direct face-to-face communication. Second, the use of adaptive language style according to the communication context, and communication symbols using verbal signs through text and non-verbal signs through emoji symbols. Third, the formation of the image of the millennial generation is done by managing speech, writing, comments, and emojis based on the values of honesty and openness. The contribution of this research is that there is a map of shifts in social communication patterns from direct face-to-face communication patterns to internet-based and social media-based communication patterns.